Managers and Management in Vietnam: 25 Years of Economic Renovation (Doi moi), 1st edition - Edwards, Vincent (Routledge, 2020)
This book presents a comprehensive overview of managers and management in Vietnam, based on extensive original research, including interviews with a large number of managers in Vietnam. It shows how management in Vietnam is best understood from the perspective of Vietnamese managers themselves, rather than in terms of Western or Asian models of management. It discusses the range of enterprises in the Vietnamese economy, which, until 1986, was dominated by large state-owned enterprises and Soviet-style central economic planning, and where there is now a much greater variety, with a mix of privatised state-owned enterprises, foreign-owned companies, joint ventures and a very large number of relatively small private companies, all operating in a social market economy where Party ideology emphasises a balance between economic growth and workers’ rights. The book demonstrates how the tensions arising from this economic landscape are reflected in the views and actions of managers as they balance economic and social goals in their work, and how their activities are constrained further by the enduring influence of local culture which is not always amenable to imported ideas and methods. As many managers have worked in different kinds of companies, the book also reveals a great deal about management in different contexts and also about how companies have changed as the reform process has evolved.